Perbandingan Penggunaan Tenaga bagi Bangunan Hijau ‘Diamond Building’ dengan Bangunan Pejabat Konvensional di Malaysia - Shahron, Alif Hilmi; Wee, Seow Ta (Research in Management of Technology and Business, 2020)
The headquarters of the Malaysian Energy Commission in Putrajaya is one of the most accredited buildings in the Green Building Index (GBI). One of the novelity of Diamond buildings is their lower BEI performance compared to other office buildings. This study was conducted to look at the comparative use of Diamond building energy and conventional office buildings. The question from this study is how energy consumption is used in Diamond building and conventional office building and what are the steps taken by both buildings to save energy. The objectives of the study were to identify energy consumption in the diamond building and conventional office buildings and to identify energy saving measures in both office buildings. Therefore, this study examines the use of qualitative methods as the primary source for data acquisition. Respondents consisted of 2 experienced and knowledgeable people in the the building being studied. The results of this study found that generally the energy consumption for these two buildings are from the use of air conditioning, electrical and electronic equipment and mechanical equipment and what distinguishes these two buildings is the system used to operate the equipment. The energy management involves monitoring energy consumption, consumer discretion in selecting appropriate equipment, the knowledge of clients, architects, engineers and contractors on architecture and sustainable construction and cooperation of building occupants. This study can provide inspiration and benchmarks for other buildings in the management of energy consumption in the building and measures to reduce energy consumption. The data and information collected may be used by facility managers, building supervisors, technicians and related members as reference.